Retroperitoneal Spindle Cell Tumor: A Case Report - Hua, Hao; He, Zhiwei; Lei, Linhan; Xie, Huahua; Deng, Zilei; Cheng, Zili; Zuo, Shi; Sun, Chengyi; Yu, Chao (Frontiers in Surgery, 2021)
Spindle cell tumor is very rare. Herein we report a case of retroperitoneal spindle cell tumor in a 52-year-old female. The patient first presented with a complaint of persistent pain in the right upper abdomen. As follow-up, CT scan was performed which showed a retroperitoneal soft tissue density mass measuring 11cm in diameter was found. And then, the subsequent surgery was conducted, we completely resected the tumor and part of the invaded lesions. The tumor histologically diagnosed of a spindle cell tumor. Therefore, it is crucial for us to enhance the understanding of this seldom found tumor. Surgery remains the best option for the treatment.